Impact of Customer Orientation on Medical Services, Infrastructure and Communication Dimensions of Service Quality in Hospitals: A Case Study of Chandigarh Tri city. - Dogra, Ajay Kumar (Gyan Management Journal, 2018)
Despite the importance of customer orientation and how it can influence the marketing efforts by an  organization, the research on this particular construct has not been that much. Customer orientation is  a vast term, used to cover all the components which contribute to maintain an efficient relation with  client. It doesn't mean being only aware of your clients, it also refers to the actions that need to be taken . in order to ensure they will continue to be your clients. Customer orientation has positive effects on  sales performance, quality perception by the consumer, and construction of buyer-seller relationships  and customer satisfaction. In this study, an attempt has been made to measure the impact of customer orientation practices on  three dimensions of service quality, medical services, hospital infrastructure and patient  communication. The results show that there is a significant relationship betw~en these various  dimensions of service quality with customer orientation; hence the hospitals must focus on the  customer orientation practices, so that the perception of patients and their attendants is on positive  side regarding the service quality.
Keywords: Orientation; Service Quality; Communication Dimensions